Cultivation of Nannochloropsis oceanica biomass rich in eicosapentaenoic acid utilizing wastewater as nutrient resource. (October 2016) - Mitra, Madhusree; Shah, Freny; Bharadwaj, S.V. Vamsi; Patidar, Shailesh Kumar; Mishra, Sandhya
Graphical abstract: Highlights: EPA production by N. oceanica using wastewater nutrients. Studied strain gets adapted to wastewater nutrients. Amelioration of EPA% in pesticides industry and municipal effluents. Pharmaceutical and oil industry water was found to be more desirable for biodiesel production. Selective utilization of wastewater nutrients for EPA and/or biodiesel. Abstract: The eicosapentaenoic acid rich marine eustigmatophyte Nannochloropsis oceanica was grown in wastewaters sampled from four different industries (i.e. pesticides industry, pharmaceutical industry, activated sludge treatment plant of municipality sewage and petroleum (oil) industry). Under the wastewater based growth conditions used in this study, the biomass productivity ranged from 21.78 ± 0.87 to 27.78 ± 0.22 mg L −1 d −1 in relation to freeze dried biomass, while the lipid productivity varied between 5.59 ± 0.02 and 6.81 ± 0.04 mg L −1 d −1 . Although comparatively higher biomass, lipid and EPA productivity was observed in Conway medium, the %EPA content was similarly observed in pesticides industry and municipal effluents. The results highlight the possibility of selectively using wastewater as a growth medium, demonstrating the elevated eicosapentaenoic acid content and biodiesel properties, that complies with the European standards for biodiesel.